The effectiveness and health impact of fad diets on obese patients: a literature review - Kraszkiewicz, Adrianna; Zaliwska, Dominika; Paduszyńska, Natalia; Dąbrowska, Anna; Gonciarz, Marta Justyna; Czach, Magdalena; Strojny, Agnieszka Aleksandra; Adamiec, Dominika Karolina; Kamińska, Monika Anna; Kienanh Do, Monika (Quality in Sport, 2024)
Introduction and purpose Obesity is a serious health problem nowadays and it is becoming more and more common. There are plenty of causes of obesity including bad eating habits, genetic factors, and psychological factors. A lot of obese people look for a way to lose weight. Fad diets are popular dietary strategies which are promoted as a quick way to lose weight. This article highlights some popular dietary strategies including low-carbohydrate diet, low-fat diet, Paleolithic Diet and Detox Diet. The aim of this paper is to analyse their effectiveness in the process of successful weight loss and their health impact. State of knowledge According to WHO in 2022 1 in 8 people in the world were obese. Fad diets are promoted as methods to improve health and as a quick way to lose weight. However, available research suggests a rather unfavorable impact on human health in the context of long-term adherence to these diets. Limited data suggests the beneficial long-term health impact of such diets. Moreover, dieting and weight cycling caused by the repetitive process of weight loss after dieting and weight regain afterwards may also play a role in the development of obesity. Conclusion Fad diets are not recommended as a long-term way of nutrition. The main limitation of these dietary strategies is their short-term effectiveness rather than long-term. Adherence to these diets is hard for patients. Because of their strict rules and food exclusions, the risk of weight regain is high. Moreover, they do not show many positive long-term health consequences and they are not superior to conventional healthy diets. What’s more, strict obedience to fad diets for extended periods of time may be detrimental to the dieter’s health.